Long Term Effects of Combination of Metabolite Product Amniotic Membrane Stem Cell (MP-AMSC) and Vitamin C after Fractional CO2 Laser for Photoaging Treatment - Vidyani Adiningtyas; Muhammad Yulianto Listiawan; Linda Astari (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Metabolite Products Amniotic Membrane Stem Cell (MP-AMSC) originating from the amniotic membrane has a skin rejuvenation effect by stimulating collagen synthesis. Vitamin C functions as an antioxidant in photoaging treatment. It is expected that the application of a combination of MP-AMSC and vitamin C after fractional CO2 laser treatment as Laser-Assisted Drug Delivery (LADD) to provide better long-term effects on clinical improvement of photoaged skin. As the drug penetration reaching the target, long-term effects and no side effects are expected. This promises as an option for photoaging therapy in the future. Purpose: This study aimed to evaluate the long-term effects of a combination of topical MP-AMSC mixtures and vitamin C after fractional CO2 laser treatment on wrinkles, spots, pores, and skin tones. Methods: Thirty adult women with photoaged skins were selected as samples, and were observed for wrinkles, spots, pores, and skin tones examination. The observation involved computer-simulated photographic devices, Facial Skin Scope System Janus-II for three months after the topical administration of MP-AMSC mixture and vitamin C, three times fractional CO2 laser, tretinoin 0.025% cream, and sun protection factor (SPF) 30 sunscreen as maintenance therapy. Result: The data analysis result was not statistically significant (p>0.05). Conclusion: There was a long-term effect of the application of a mixture of topical MP-AMSC and vitamin C after fractional CO2 laser treatment, and no side effect was observed.